Análise de um empreendimento de economia solidária sob a ótica da sociologia das ausências e das emergências - Marília Veríssimo Veronese (Ciências Sociais Unisinos)
This paper is a result of a doctorate research in psychology, a case study done in an urban cooperative society in Porto Alegre (RS). Its goal is to discuss the work in the solidary economy, analyzing the experiences of workers in an enterprise, as well as the subjectivity questions linked to laboral processes. Its main theoretical frames are Boaventura de Sousa Santos, with the sociology of the absences and emergencies, as well as Fernando Gonzalez Rey and Felix Guattari, with the theorizations on subjectivity, respectively understood as a process of a symbolic sense production and a social-historical production that assumes a serial pattern in the capitalist contemporaneity. The main findings, in the enterprise course analysis, show great difficulties found by the subjects who work in the solidary economy field that, although identified with alternative ways of living and working, perceive the appropriation process of self management as something beyond their possibilities. They want to differ from the capitalist management, but feel this trial as a labyrinth in which they feel lost. They also undervalue and blame themselves because of the found difficulties. The power relationships are not dialogical and asymmetrical. However, they seek possibilities of a new beginning, showing that the field presents emancipatory potentiality, where collective can permit the subjects particularization, which can be recognized and constituted by themselves.